Nanotechnology and its Application in Restorative Dentistry: A Review of Literature - Sahithi Reddy, Dhakshinamoorthy Malarvizhi2 , Alagarsamy Venkatesh2 , Paramasivam Vivekanandhan (Indian Journal of Forensic Medicine & Toxicology, 2020)
Norio Taniguchi, in 1974 coined the term ‘nanotechnology’. It includes the processing of separation,consolidation, and deformation of materials by one atom or one molecule. Nanotechnology has pavedpath for enhancing many material properties. Similarly so in dentistry it has led to enhancement of manytraditional restorative materials such as dental composite and GIC which has made it possible to use theserestorative materials in almost every region of the tooth. The aim of the present review article is to provideinsights into recent developments in the field of restorative dentistry favored by nano technology suchas, nano-composites, nano-bonding systems, nano-GIC, nano-varnish and sealants. It can be an aid to thedentist in clinical practice or in research field.